Analysis of Pro-Environmental Behavior of Residents In Household Waste Management - Dennisa Awwalia Harahap; Sarwititi Sarwoprasodjo; Dwi Retno Hapsari (Green Publisher Indonesia, 2025)
The waste problem in Indonesia is one of the major problems. Bogor City is one of the cities that has a serious waste problem. Public awareness and participation are needed to overcome the waste problem. Waste management at the Rangga Mekar Waste Bank is important for good waste management by sorting waste. Public participation in waste sorting practices is expected to reduce environmental pollution. This study aims to see the Rangga Mekar waste bank program educating and influencing the community by analyzing the influence of environmental factors of the Rangga Mekar Waste Bank on the personal factors of waste bank customers, analyzing the influence of environmental factors of the Rangga Mekar Waste Bank on the behavior of residents in managing waste, and the influence of personal factors of residents on waste management behavior. The method used in this study is the survey method. The results show that environmental factors have a positive influence in measuring personal constructs, but the influence of direct environmental factors on behavior is not significant. Personal factors have a positive influence on behavioral factors. Waste management in the community is greatly influenced by personal factors and individual self-ability. The environment acts as a reinforcer, while behavioral change depends on improving personal factors.